Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Converted-wave Kirchhoff pre-stack depth migration based on multi-wave traveltime tables - Bingkai Han; Weijian Mao; Hanming Gu (Journal of Applied Geophysics, 2026)

Asymmetric Deep Co-Training Framework Using a Shape Context Descriptor for Reservoir Prediction: A Case Study from the Yinggehai Basin, South China Sea - Xuanang Li; Jiao Xue; Hanming Gu (Journal of Marine Science and Engineering, 2026)
The scarcity and incompleteness of well-log data pose a critical challenge to deep learning-based reservoir prediction. To address this small-sample problem and improve prediction quality, we propose a novel semi-supervised asymmetric deep co-training framework integrated with a shape context descriptor. This method leverages abundant unlabeled seismic data as well as complementary information on related physical properties. Specifically, we introduce a shape context descriptor to encode seismic waveform morphology and spatial context, thereby improving the lateral continuity and interpretability of predictions while mitigating issues inherent in the sequence-to-point paradigm, wherein three-dimensional seismic data are used as input and a single target point is predicted. To overcome data limitations, a sliding-window resampling strategy is employed to expand the training samples. For co-training, we design an asymmetric dual-task architecture wherein one model performs porosity regression while the other conducts reservoir type classification, thereby enabling synergistic learning. The proposed framework is validated using real three-dimensional seismic data from the Yinggehai Basin in the South China Sea through ablation experiments. The results demonstrate superior performance in prediction accuracy, spatial consistency, and training stability compared to baseline methods.

U-Net3+ with full-scale fusion and deep supervision for seismic noise suppression - Wei Wang; Zhiyuan Gu; Qianggong Song; Hanming Gu (Journal of Applied Geophysics, 2026)

An effective deep domain adaptation approach for least squares migration - Wenjun Ni; Shaoyong Liu; Zhikang Zhou; Hanming Gu; Bin Zhang (Computers & Geosciences, 2026)

A high-efficiency topography anisotropic wave separation elastic reverse time migration method - Yu Zhong; Qinghui Mao; Kun Zou; Hongyu Zhou; Mei He; Kai Xu; Hanming Gu; Zeyun Shi; Yuan Zhou; Haibo Huang (Acta Geophysica, 2026)

An effective workflow for deblending simultaneous source marine data using the seislet transform - Kun Zou; Jianhua Wang; Yueyue Wang; Shuaibing Li; Yandong Wang; Yu Zhong; Hanming Gu; Haibo Huang; Yuan Zhou (Acta Geophysica, 2025)

Deep-sea oil and gas plow-type cable broadband wide-azimuth 3D seismic acquisition and imaging - Yunfei Ye; Li-Yun Fu; Lijun Mi; Chuncai Chen; Zhenhua Jiao; Hanming Gu; Yu Wu (Science China Earth Sciences, 2025)

Reducing the Effect of Incorrect Lithology Labels on the Training of Deep Neural Networks for Lithology Identification - Xiaoyue Feng; Hongmei Luo; Changjiang Wang; Hanming Gu (Mathematical Geosciences, 2024)

Anisotropic elastic least-squares reverse time migration with density variations in vertical transverse isotropic media - Yu Zhong; Hanming Gu; Yangting Liu; Xia Luo; Qinghui Mao; Kai Xu (Acta Geophysica, 2023)

A new elastic least-squares reverse-time migration method based on the new gradient equations - Yu Zhong; Yangting Liu; Hanming Gu; Qinghui Mao (Acta Geophysica, 2022)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

An integrated approach for the identification of lithofacies and clay mineralogy through Neuro-Fuzzy, cross plot, and statistical analyses, from well log data - Muhsan Ehsan; Hanming Gu (Journal of Earth System Science, 2020)

Identification of Hydrocarbon Potential of Talhar Shale: Member of Lower Goru Formation Using Well Logs Derived Parameters, Southern Lower Indus Basin, Pakistan - Muhsan Ehsan; Hanming Gu; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Zaheen Ullah (Journal of Earth Science, 2018)